Análise da cinemática de corredores adultos jovens e idosos - Thiago Ribeiro Teles dos Santos (2011)
The kinematics of elderly runners might represent the strategies used to produce sports motion due to their physiological and biomechanical characteristics. The investigation of pelvis and lower limb motion in elderly runners could help to understand the differences observed between elderly and adults during running. The aim of this study was to investigate the differences of spatio-temporal characteristics and kinematics of the pelvis and lower limb during running between elderly and younger adult runners. A cross-sectional study was conducted with 20 young adult runners (25.85 ± 3.69 years old) and 20 elderly runners (65.30 ± 4.22 years old). During data collection of running, participants ran on a treadmill with self-selected speed. The demographic and training features, as well as self-selected speed of each group were presented as mean and standard deviation. The difference between groups in these variables was investigated by independent t test. The dependent variables were presented as mean and standard deviation, and are grouped as spatio-temporal, position in initial contact, position in toe-off and range of motion (ROM) in contact phase. For each group of these variables, multivariate analysis of covariance considering the self-selected speed as covariate was performed. In presence of main effect, univariate tests were performed to investigate which variables were different between groups of runners. The ROM variables which showed differences between groups were represented in graphs of their time series. The results indicated a reduction of stride total time and length, contact phase time and length, and increased stride frequency in elderly compared to adults (p<0,01). The angular variables did not differ between groups in initial contact (p=0,11), but were different in toe-off (p<0,01). At this phase, there was less hip extension (p<0,01) and more knee abduction (p=0,01) in elderly. Furthermore, elderly runners showed a reduction in ROM of hip in its three planes of motion (p0,05) and tibia-rearfoot angle in transverse plane (p=0,02) when compared to young adults. In conclusion, the difference in spatio-temporal variables indicates that the running pattern of elderly is characterized by a system stiffer and with less capability to produce force. Moreover, the results show differences in kinematics variables between elderly and young adults runners, mainly in hip variables, which might also be related to a reduced capability to generate force by elderly runners